Innovative methodologies and ICT mediation: Challenges in the careers of the University of Managua - Canales, Helga Mercedes Navarro; Flores, Pablo Emilio Hurtado; Pulido, Alvin López (Advanced Notes in Information Science, 2024)
Innovative methodologies for the teaching–learning process, making use of information and communication technology (ICT) in undergraduate courses at the University of Managua (UdeM), has focused on the design and development of relevant technological tools. The objective is to contribute to the design of relevant technological tools and didactic situations that facilitate the implementation of innovative learning and teaching methodologies at the UdeM and the development of skills from a transformative, integral, and permanent perspective for the achievement of quality in teacher training as a strategic teacher. The research assumes a qualitative approach, diagnosing the needs and challenges in the implementation of innovative methodologies by teachers in the teaching–learning process at the UdeM. The findings obtained have allowed the development of pertinent resources and didactic proposals, providing teachers with tools to improve the quality of training and promote active and meaningful learning of students. The main results were obtained. The paper is the result of a research project, which has contributed to the advancement of higher education through the effective integration of ICT in undergraduate courses at the UdeM, promoting transformation and continuous improvement in teaching.